Pulsed-Field Gel Electrophoresis Is More Efficient than Ribotyping and Random Amplified Polymorphic DNA Analysis in Discrimination of Pasteurella haemolytica Strains - Kodjo, Angeli (American Society for Microbiology, 1999)
One hundred thirty-three strains of Pasteurella haemolytica of both biotypes (90 and 43 strains of biotypes A and T, respectively) and almost all the serotypes were subjected to ribotyping, random amplified polymorphic DNA (RAPD) analysis, and pulsed-field gel electrophoresis (PFGE) analysis for epidemiological purposes. A total of 15 patterns recorded as ribotypes HA to HO were found for the P. haemolytica biotype A strains, with ribotypes HA, HC, and HD being encountered most often (66 strains [74%]); and 20 ribotypes, designated HA′ to HT′, that were clearly distinct from those observed for biotype A strains were observed for strains of biotype T. RAPD analysis generated a total of 44 (designated Rp1 to Rp44) and 15 (designated Rp1′ to Rp 15′) unique RAPD patterns for biogroup A and biogroup T, respectively. Analysis of the data indicated that a given combined ribotype-RAPD pattern could be observed for biotype A strains of different serotypes, whatever the zoological or geographic origin, whereas this was not the case for biotype T strains. PFGE appeared to be more efficient in strain discrimination since selected strains from various zoological or geographical origins harboring the same ribotype-RAPD group were further separated into unique entities.